Randomised Phase 2 study of lapatinib and vinorelbine vs vinorelbine in patients with HER2 + metastatic breast cancer after lapatinib and trastuzumab treatment (KCSG BR11-16) - Sim, Sung Hoon (Br J Cancer, 2019)
BACKGROUND: The continuum of anti-HER2 agents is a standard treatment of HER2 + metastatic breast cancer (MBC). This study evaluated the efficacy of lapatinib plus vinorelbine in patients progressed on both trastuzumab and lapatinib treatments. METHODS: A total of 149 patients were randomly assigned to lapatinib with vinorelbine (LV) (n = 75; lapatinib, 1000 mg daily; vinorelbine 20 mg/m(2) D1, D8 q3w) or vinorelbine (V) (n = 74; 30 mg/m(2) D1, D8 q3w). The primary endpoint was progression-free survival (PFS) rate at 18 weeks. RESULTS: The median number of previous anti-HER2 therapies was 2 (range 2–5). There was no significant difference in PFS rate at 18 weeks between LV and V arms (45.9% vs 38.9%, p = 0.40). ORR was 19.7% in LV arm, and 16.9% in V arm (p = 0.88). PFS and OS did not differ between two arms (LV vs V; median PFS, 16 vs 12 weeks, HR = 0.86, 95% CI 0.61–1.22; median OS, 15.0 vs 18.9 months, HR = 1.07, 95% CI 0.72–1.58). Toxicity profiles were similar in both arms and all were manageable. CONCLUSIONS: Lapatinib plus vinorelbine treatment was tolerable; however, it failed to demonstrate the clinical benefits over vinorelbine alone in patients with HER2 + MBC after progression on both trastuzumab and lapatinib. CLINICAL TRIAL REGISTRATION: ClinicalTrials.gov number NCT01730677.